An examination of the political salience of corporate tax avoidance: A case study of the Tax Justice Network. Issue 4 (1st December 2017) - Dallyn, Sam
Abstract: Corporate tax avoidance (CTA) has become a high profile issue despite being a complex area of accounting practice. One reason for this has been the civil society campaign opposing tax avoidance. The paper provides a case study of one key civil society actor: the Tax Justice Network (TJN). Existing accounting analysis offers little to explain how some accounting issues acquire political attention and media coverage. To address this, the concept of political salience is introduced into accounting analysis – understood as the creation of focal points in campaigns – to consider how the TJN contributed to the political profile of CTA.